Post-COVID-19 patients in geriatric rehabilitation substantially recover in daily functioning and quality of life - van Tol, Lisa S; Haaksma, Miriam L; Cesari, Matteo; Dockery, Frances; Everink, Irma H J; Francis, Bahaa N; Gordon, Adam L; Grund, Stefan; Matchekhina, Luba; Bazan, Laura Monica Perez; Schols, Jos M G A; Topinková, Eva; et al. (Age and ageing, 2024)
BACKGROUND: After an acute infection, older persons may benefit from geriatric rehabilitation (GR). OBJECTIVES: This study describes the recovery trajectories of post-COVID-19 patients undergoing GR and explores whether frailty is associated with recovery. DESIGN: Multicentre prospective cohort study. SETTING: 59 GR facilities in 10 European countries. PARTICIPANTS: Post-COVID-19 patients admitted to GR between October 2020 and October 2021. METHODS: Patients' characteristics, daily functioning (Barthel index; BI), quality of life (QoL; EQ-5D-5L) and frailty (Clinical Frailty Scale; CFS) were collected at admission, discharge, 6 weeks and 6 months after discharge. We used linear mixed models to examine the trajectories of daily functioning and QoL. RESULTS: 723 participants were included with a mean age of 75 (SD: 9.91) years. Most participants were pre-frail to frail (median [interquartile range] CFS 6.0 [5.0-7.0]) at admission. After admission, the BI first steeply increased from 11.31 with 2.51 (SE 0.15, P < 0.001) points per month and stabilised around 17.0 (quadratic slope: -0.26, SE 0.02, P < 0.001). Similarly, EQ-5D-5L first steeply increased from 0.569 with 0.126 points per month (SE 0.008, P < 0.001) and stabilised around 0.8 (quadratic slope: -0.014, SE 0.001, P < 0.001). Functional recovery rates were independent of frailty level at admission. QoL was lower at admission for frailer participants, but increased faster, stabilising at almost equal QoL values for frail, pre-frail and fit patients. CONCLUSIONS: Post-COVID-19 patients admitted to GR showed substantial recovery in daily functioning and QoL. Frailty at GR admission was not associated with recovery and should not be a reason to exclude patients from GR.
Keywords: Male; Evropa; geriatrické hodnocení; Quality of Life; křehkost; SARS-CoV-2; Europe; senioři nad 80 let; Geriatric Assessment; ženské pohlaví; činnosti denního života; obnova funkce; recovery; Aged; prospektivní studie; Prospective Studies; older people; COVID-19; Humans; Frailty; senioři; kvalita života; Female; mužské pohlaví; Recovery of Function; Activities of Daily Living; křehký senior; geriatric rehabilitation; Frail Elderly; lidé; Aged, 80 and over